2022
DOI: 10.1007/s10758-022-09603-z
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Traditional to Online Learning in Hong Kong Tertiary Educational Institutions During COVID-19 Pandemic

Abstract: The adoption of online learning approach in education is becoming more popular around the world to overcome the time and spatial barriers of traditional face-to-face learning. The Coronavirus Disease 2019 (COVID-19) pandemic has affected the normality of learning and avoiding face-to-face activities is one tactic to minimise the spread of COVID-19. This study investigated the perception of online learning from students’ and teachers’ perspectives compared to traditional face-to-face learning during the COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Therefore, it can be adapted easily for any courses to many advantages. For instance, Law et al, ( 2022 ) in Hong Kong examined the students’ and teachers’ perceptions on online learning compared to face-to-face learning during Covid-19 and observed that from the teachers’ perspective, online learning depended on technical devices and systems that created stress and influenced teaching quality. As a result, Dang et al, ( 2020 ) concluded that it is the best to combine the face-to-face teaching with the positive aspects of online learning.…”
Section: Research In Vc Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be adapted easily for any courses to many advantages. For instance, Law et al, ( 2022 ) in Hong Kong examined the students’ and teachers’ perceptions on online learning compared to face-to-face learning during Covid-19 and observed that from the teachers’ perspective, online learning depended on technical devices and systems that created stress and influenced teaching quality. As a result, Dang et al, ( 2020 ) concluded that it is the best to combine the face-to-face teaching with the positive aspects of online learning.…”
Section: Research In Vc Learningmentioning
confidence: 99%
“…The flexibility which comes with virtual learning is one hugely positive factor but can contribute to many of the other issues such as difficulty in communication and lack of connection with instructors (Swanson et al, 2021 ) Tang et al, ( 2020 ) found that when students came up against difficult topics, more traditional teaching methods were better than online teaching. Similarly, in a study of Hong Kong tertiary educational institutions, Law et al, ( 2022 ) concluded that teacher-student and student–teacher interactions were the biggest challenge in online learning that affected the acquisition and application of knowledge. The lack of hands-on experience was seen to be a drawback of virtual learning in the UAE (Al-Karaki et al, 2021 ) In a study by Swanson et al, ( 2021 ) looking at student’s experiences of the move from face to-face to distance learning in two universities in the United States, found that many students required more input, feedback and assurance from professors on the course.…”
Section: Advantages and Drawbacks Of Vc Learningmentioning
confidence: 99%
“…7), in PISA that kind of data was not. To analyse learning approaches and curricula, not widely countries focus on students enjoyment learn specific subject, although during Covid-19 pandemic, some of the countries analyse the data from students and the teachers about online learning and what have caused most of the stress during this time (for example, Law, Yee, Ng, Fong 2022;Tan, Chua, 2022;Lin, Chen, Liu, Chang, 2022). Well-being is related to income.…”
Section: Resultsmentioning
confidence: 99%
“…Thoughts and ideas must be communicated for better outcomes and students' awareness. The flexibility of online classes does not mean they provide efficient and purposeful learning; hence, individual differences of the students affect their learning styles (Law et al, 2022). Table 6 shows that significant differences exist between the pre-test and post-test results of classifying and measuring among the six BSPS.…”
Section: Findings and Discussionmentioning
confidence: 99%